1992
DOI: 10.1080/00222895.1992.9941614
|View full text |Cite
|
Sign up to set email alerts
|

Information Feedback and the Learning of Multiple-Degree-of-Freedom Activities

Abstract: The influence of information feedback on the learning of a multiple-degree-of-freedom activity, the overhand throw, was investigated. During learning, feedback was presented in the form of knowledge of results, knowledge of performance, knowledge of performance with attention-focusing cues, or knowledge of performance with error-correcting transitional information. Across 12 practice sessions, performance was assessed with respect to both throwing distance and throwing form. Subjects provided with knowledge of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0
18

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 16 publications
6
80
0
18
Order By: Relevance
“…Assuming the use of a feedback, the increase observed in the scores of the Verbal and the Video groups is approximately two times bigger than the Control group one. This result confirms earlier studies, when providing feedback on the error movement generated corrections on the next move, approximating the movement to the goal task and improving performance 17,[21][22][23][24][25] . Analyzing the mean and the coefficient of variation of the scores in Retention, we observed that the Verbal group learning was superior to the Control group learning.…”
Section: Learning Assessmentsupporting
confidence: 80%
See 2 more Smart Citations
“…Assuming the use of a feedback, the increase observed in the scores of the Verbal and the Video groups is approximately two times bigger than the Control group one. This result confirms earlier studies, when providing feedback on the error movement generated corrections on the next move, approximating the movement to the goal task and improving performance 17,[21][22][23][24][25] . Analyzing the mean and the coefficient of variation of the scores in Retention, we observed that the Verbal group learning was superior to the Control group learning.…”
Section: Learning Assessmentsupporting
confidence: 80%
“…It was not clear that the videotape feedback has a motivational effect superior to the verbal feedback. However, due to some participants, in the Control group, have considered learning the breaststroke tiring and were not satisfied with it, we evidenced, as well as in initial researches [16][17][18] , that the use of feedback has a superior motivational effect than the situation in which it is not provided 12 . Another important aspect was that six participants of the Control group failed to participate in the experiment without any justification, raising the question about their motivational states to practice without providing feedback.…”
Section: Motivation Assessmentmentioning
confidence: 82%
See 1 more Smart Citation
“…Most of what we know about providing augmented feedback comes from laboratory experiments in which KR was manipulated. 22 Some researchers 16,55 have suggested that KP is better than KR at facilitating skill acquisition, whereas others 42 demonstrated the benefit of both KR and KP, each providing benefit for different reasons. Researchers that have assessed the use of RUSI to assess the anterolateral abdominal and lumbar multifidus muscles have used both KR and KP (TABLE).…”
Section: Feedback To Enhance Motor Performance and Motor Learningmentioning
confidence: 99%
“…Rikli e Smith (1980) CARLTON, 1992;ROTHSTEIN, 1980;ROTHSTEIN;ARNOLD, 1976) e crianças (BUNKER et al, 1976;NEUFELD;NEUFELD, 1972).…”
Section: Discussão E Conclusãomentioning
confidence: 99%